Complex battlespaces : the law of armed conflict and the dynamics of modern warfare - Ford, Christopher M.; Williams, Winston S. (Lieber Institute for Law and Land Warfare book series, 2019)
The conduct of warfare is constantly shaped by new forces that create complexities in the battlespace for military operations. This inaugural volume of the Lieber Studies Series seeks to address several issues in the confluence of law and armed conflict, featuring chapters from world class scholars, policymakers and other government officials; military and civilian legal practitioners; and other thought leaders who examine the role of the law of armed conflict in current and future armed conflicts around the world.